“If you show your real face, you’ll lose 10 000 followers” – The Gaze of the Other and Transformations of Shame in Digitalized Relationships - King, Vera (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2016)
This essay examines the significance and transformation of shame in the context of digitalization, in particular, the psychosocial and psychological consequences of shifts in the boundaries between public and private manifest in the contemporary digital world. Moreover, it will examine the dynamic relationships of shame, humiliation and shamelessness as they develop in digital environments characterized by the dissolution of physical and communicative presence, as well as the, in turn, changing functions, ambivalences and affective pitfalls of self-presentation. On the basis of descriptions and commentaries by contemporary adolescents on the significance of social networks and on their own digital self-presentation, it will identify mechanisms for dealing with the imagined, projected or abnegated gaze of the other in the Net.